Squamous cell carcinoma of the renal pelvis presenting as an integumentary neoplasm of the flank: A case report. Issue 36 (September 2019) - Kim, Jung Ryul; Jeong, Young Beom; Lee, Nae Ho; Wang, Sung Il
Abstract: Rationale: Although chronic pyelonephritis and urolithiasis are established risk factors for squamous cell carcinoma (SCC), only a minority of patients with chronic urolithiasis eventually develop SCC. It is believed that the chronic irritation leads to squamous cell metaplasia that may subsequently develop into SCC. Although studies show that SSC generally spreads locally with associated symptoms of lymphadenopathy, metastasis to the lungs and liver have also been reported. However, cases spreading to the flank have yet to be reported. Therefore, the use of reconstructive techniques for the repair of extensive soft tissue defects in the flank region after extended retroperitoneal resection, is unknown. Patient concerns: We report a 54-year-old man who presented with a 1-month history of an enlarged skin mass on the right flank. Diagnoses: The patient was subsequently diagnosed with metastatic SCC involving the patient's integumentary system near the flank region proximal to the right kidney following percutaneous nephrostomy. Interventions: The skin mass and the surrounding muscle tissue of the right flank were excised with a wide resection margin including radial nephrectomy. The soft tissue defect after resection was reconstructed using a unilateral gluteus maximus myocutaneous V-Y advancement flap. Outcomes: No recurrence of the SSC was found on follow-up CT performed 12 months postoperatively. Lessons: In patients with long-standing nephrolithiasis complicated by staghorn stone-related infections, biopsies from suspicious lesions detected during percutaneous nephrolithotomy may facilitate early diagnosis. The modified gluteus maximus V-Y advancement flap may be a useful technique for the reconstruction of extensive soft-tissue defects involving the flank region.